Cultural Competency in a Legal Service and Justice Agency for Aboriginal Peoples - John Rawnsley; David Woodroffe; Eloise Culic; James Richards; Lauran Clifton (Legal Education Review)
The cultural characteristics of Aboriginal groups are significantly diverse and the interface between Aboriginal people and the dominant Australian culture and justice system is highly complex. The justice system, and its many parts, interacts with Aboriginal people and culture in many different ways, and is imposing. The consideration of cultural competency is necessary in understanding how justice is applied in Australia. The organisation considered by this paper delivers legal services and justice agency programs to Aboriginal people. As a non-government community organization, it is one part of a broader justice system. Governed by an Aboriginal board, the service is in a unique position to use its cultural authority to influence how cultural competency is understood from a public policy and law reform context. The service recently implemented a Cultural Competency Framework 2017-2020 (Framework) as an iterative process to outline how it is a culturally appropriate organization. The framework includes a series of strategies and actions with mechanisms for accountability. This paper will explore the legal service’s organizational approach to developing cultural competency and its application to the provision of legal aid services and justice programs. In turn, it serves as a valuable example of how a legal organisation can make a meaningful commitment to developing cultural competency. So long as Aboriginal issues or people are referred to in any context, consideration of the suitability of how an organisation approaches cultural competency, and develops its people, is relevant.